IMPLEMENTASI KURIKULUM MUATAN LOKAL Dl SEKOLAH - Suyitno Al. Suyitno Al. (Jurnal Cakrawala Pendidikan, 1999)
The eletnenta~ye ducation's Local Content Curriculuii(LCC), initiated in 1987 and renewed in 1994, whicli constitutes20% of the National Curriculum, has the strategichnction of giving elementary education the content or colorthat will make it fit the needs ofregional development. LCCwill result in students who understand the problems of dcvelopmentin their area.The implementation of LCC all this time has been verylimited because of various constraints. 'The constraiilts p;lrtl)come from the limited capabilities of schools. the lack ofsupport from tlie Department of Education and Culture, andthe utideveloped cooperation between schools and the surroundingcommunity.Culture need to take are conducting teachers' upgrading,providing facilities, and assisting tlie develotiient of cooperationbetween one school and another and between schoolsand society or other relevant institutions. The i~iiprovementon the quality of LCC's implementation at schools will hopefullyproduce students who understand the potentials andneeds of regional develop~nenat nd possess useful basic skillsso that they can participate in tlie national development.